Women’s Empowerment Through Virgin Coconut Oil Entrepreneurship in Rural West Sumatra - Anas Habibi Ritonga; Esli Zuraidah Siregar; Nurharisyah Hasibuan (Smart Society, 2025)
Women's empowerment is an important strategy for improving the economic well-being of communities, particularly in rural areas such as Nagari Katapiang, Batang Anai District, Padang Pariaman Regency, West Sumatra Province. One form of empowerment developing in this area is through the development of Micro, Small, and Medium Enterprises (MSMEs) based on Virgin Coconut Oil (VCO) production. This study aims to analyze the contribution of VCO entrepreneurship to women's empowerment and identify challenges and opportunities in developing these businesses. The method used is a qualitative approach with phenomenological techniques, supported by data analysis using NVIVO software. Data were collected through in-depth interviews, field observations, and literature studies. The results show that women's involvement in VCO production and management contributes to increasing household income, economic independence, and their social role in the community. However, women still face various obstacles, such as limited access to markets, business capital, and production technology. The findings also indicate that synergy between the government, financial institutions, and educational institutions is essential to overcome these obstacles. The conclusion of this study emphasizes that VCO entrepreneurship has the potential to be a sustainable model for women's empowerment, particularly if supported by skills training, technological innovation, and access to markets and capital.